How many bound valence states does the C60− anion have? - Gromov, Evgeniy; Klaiman, Shachar; Cederbaum, Lorenz S. (Physical chemistry, chemical physics, 2016)
We report on unprecedentedly large coupled cluster calculations for the C60− anion, and on a heuristic model uncovering the valence states of C60− that allow the resolution of the headlined question. Our results convincingly demonstrate that C60− possesses as many as four bound valence states: 2T1u, 2T1g, 2T2u and 2Hg. Our findings reconcile previous controversies regarding the existence of the bound 2T2u and 2Hg states. For all bound states of C60− we present an analysis of the radial and angular distributions of the excess electron, which reveals some unique properties of the valence states. Some interesting features of the introduced model are analyzed and discussed.
Im Titel ist "60" tiefgestellt, das Minuszeichen hochgestellt
Gesehen am 10.08.2020